Seamless Start-Up of a Grid-Connected Photovoltaic System Using Module-Integrated Micro-Converters - Leonardo Callegaro; Trung-Hieu Uong; Sara Deilami (Energies, 2023)
In traditional grid-tied photovoltaic (PV) installations, when partial shadowing occurs between different PV modules in a string, bypass diodes short-circuit the output terminals of shadowed modules, and the whole system forgoes their potential energy production. This loss can be recovered if a dc-dc converter (micro-converter) is coupled to every PV module, and operated at the maximum power point (MPP). In this scenario, without communication links between the distributed micro-converter and the grid-tied inverter, a start-up procedure must be carefully designed to seamlessly allow the system to transfer PV power to the grid. During this phase, potentially damaging over-voltages and abrupt transients occurring at the micro-converters/inverter interface must be avoided. In this paper, the control algorithm of each micro-converter is enhanced to provide a smooth start-up operation so that PV units can safely start transferring power to the inverter and the grid. Improving from previous works, the proposed control technique is simple and removes the need for current sensors at the output of each micro-converter and at the inverter dc-link, with an economical advantage. Simulation results demonstrate the successful system start-up behavior, whilst confirming the benefits of the proposed control technique. First, the dc-link is energized from the rectified grid voltage. Then, the micro-converters raise the dc-link voltage so that the available PV power is transferred to the grid, with this sequence of operations not causing any abrupt electrical transient. The results also demonstrate the robust behavior of the PV system under non-uniform solar irradiation conditions.